Adherence of ticagrelOr in real world patients with aCute coronary syndrome: The AD-HOC study. (October 2022) - Fiocca, Luigi; Rossini, Roberta; Carioli, Greta; Carobbio, Alessandra; Piazza, Isabelle; Collaku, Elona; Giubilato, Simona; Amico, Francesco; Molfese, Maria; De Benedictis, Mauro; Calabria, Paolo; Limbruno, Ugo; et al.
Abstract: Background: Dual antiplatelet therapy (DAPT) with aspirin and a P2Y12 receptor antagonist is the cornerstone of therapy in patients with acute coronary syndrome (ACS). Adherence to medical therapy is an important issue, as premature DAPT discontinuation increases the risk of new ischemic events. The aim of the present observational prospective multicenter study was to evaluate in the real-world incidence and discontinuation patterns of ticagrelor during the first 12 months after ACS. Methods: We analyzed 431 ACS patients, discharged with ticagrelor, by 7 Italian centers. The primary end-point was the incidence of cessation of ticagrelor up to 12 months from the index event. Results: Definitive ticagrelor cessations occurred in 52 patients (12.1%), of which 35 were discontinuations (clinically driven) and 17 disruptions (due to acute events). Temporary cessation occurred in 14 cases (3.3%). Age ≥ 80 years and anticoagulant therapy were independent predictors of premature discontinuation. Bleeding occurred in 74 patients, of which 25 suffered a BARC ≥ 2 bleeding event. Bleeding were more frequent in female sex (27.0% vs 17.2%, p-value 0.049) and in patients with a history of bleeding (8.1% vs 2.9%, p-value 0.035). Conclusions: Our study found that the adherence to DAPT with ticagrelor after an ACS is still an important issue, premature discontinuation occurred mainly in fragile patients, like elderly, who suffered a previous bleeding or underwent previous percutaneous coronary intervention.